NCS-1 Deficiency Is Associated With Obesity and Diabetes Type 2 in Mice - Ratai, Olga; Hermainski, Joanna; Ravichandran, Keerthana; Pongs, Olaf (Frontiers in Molecular Neuroscience, 2019)
Neuronal calcium sensor-1 (NCS-1) knockout in mice (NCS-1-/- mice) evokes behavioral phenotypes ranging from learning deficits to avolition and depressive-like behaviors. Here we showed that with onset of adulthood NCS-1-/- mice gain considerable weight. Adult NCS-1-/- mice are obese, especially when fed a high-fat diet (HFD), are hyperglycemic and hyperinsulinemic and thus develop a diabetes type 2 phenotype. In comparison to wild type NCS-1-/- mice display a significant increase in adipose tissue mass. NCS-1-/- adipocytes produce insufficient serum concentrations of resistin and adiponectin. In contrast to wild-type litter mates, adipocytes of NCS-1-/- mice are incapable of up-regulating insulin receptor concentration in response to HFD. Thus, HFD-fed NCS-1-/- mice exhibit in comparison to wild-type litter mates a significantly reduced insulin receptor expression, which explains the pronounced insulin resistance observed especially with HFD-fed NCS-1-/- mice. We observed a direct correlation between NCS-1 and insulin receptor concentrations in adipocyte membrane and that NCS-1 can be co-immunoprecipitated with insulin receptor indicating a direct interplay between NCS-1 and insulin receptor. We propose that NCS-1 plays an important role in adipocyte function and that NCS-1 deficiency gives rise to obesity and diabetes type 2 in adult mice. Given the association of NCS-1 with psychiatric disorders and the behaviorial abnormalities of NCS-1-/- mice they offer a promising perspective for future studies on potential genetic links between psychiatric disorders and the risk of being obese.